ANALISIS KUALITAS AIR TELUK PEGAMETAN BALI BERDASARKAN METODE INDEKS PENCEMARAN - Dewi, Ni Luh Putu Tania; Angga Pebriani, Dewa Ayu; Wiweka Krisna Dewi, Ayu Putu (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 18 No 2 (2024)DO - 10.24843/EJES.2024.v18.i02.p06, 2024)
The assessment of water quality holds immense significance, especially in areas with high levels of activity such as fisheries cultivation zones. The introduction of waste from Floating Net Cage vessels and ponds could lead to a decline in water quality within Pegametan Bay. The health and survival of the varied species inhabiting the bay heavily rely on maintaining optimal water quality. This research aims to assess the existing water quality and create pollution indices by analyzing both physical and chemical parameters within Pegametan Bay.Employing a quantitative methodology, water samples were obtained from 6 distinct stations and assessed against the seawater quality standards specified in Government Regulation No. 22 of 2021. Subsequently, pollution index methodologies were applied to analyze these findings.The analyzed water quality indicators are temperature, pH, dissolved oxygen (DO), turbidity, Total Suspended Solids (TSS), Biochemical Oxygen Demand (BOD), nitrate, ammonia, and salinity. Measurements were carried out directly on the water surface (temperature, pH, DO, turbidity, and salinity) as well as in samples taken to the Kerthi Bali Sadhajiwa Provincial Health Laboratory (TSS, BOD, nitrate, and ammonia). Measurement results indicate that temperature varied from 29.9 to 31.5°C; pH varied from 8.4 to 8.5; DO varied from 5 to 6.5 mg/L; turbidity varied from 0.35 to 0.70 NTU; TSS varied from 1 to 3 mg/L; BOD ranged from 0.60 to 1.01 mg/L; nitrate ranged from 0.394 to 0.4 mg/L; ammonia ranged from 0.001 to 0.038 mg/L; and salinity ranged from 30 to 33 ppt. Most of the measurements show good water quality, meeting the standards necessary to support marine life. According to the Minister of Environment Decree No. 115, year 2003, on Determination of Water Quality Status, pollution index values at all research stations were found in the range between 2.62 and 2.91. Based on the average score, all research stations were categorized as lightly polluted, with station 5 having the highest pollution index (2.91) and station 4 having the lowest (2.62). Keywords: Fishing Activities; Pegametan Bay; Pollution Index; Water Quality